PEMANFAATAN TEPUNG TEMPE DALAM PEMBUATAN COOKIES KAYA PROTEIN DAN SERAT - Annisa Putri Larasati; Debby Endayani Safitri (UHAMKA PRESS, 2017)
Decreasing in protein consumption and low consumption of fber was one of the nutritionalproblems in the community, especially in young adults. One of solutions to solve its problem,namely by making food products with a source of protein and fber derived food ingredients suchas ﬂour. The purpose of this study was to examine the use of tempeh ﬂour as a substitutematerial in the production of cookies as a food product with a source of protein and fber. Theamount was, i.e. 70%, 80% and 90% of tempeh ﬂour that had substituted to wheat ﬂour.Organoleptic test with semi-trained panelists had done to elect the best cookies formula. This studyused complete randomized experimental design (CRD) with one factor and two replications. Theresults of this study is higher substitution of tempeh ﬂour to wheat ﬂour would produce lowerquality of color, texture, ﬂavor and aroma of cookies and lower panelist preference level of color,texture, ﬂavor and aroma of cookies. Based on the hedonic product quality assessment,the elected cookies with 70% substitution of tempeh ﬂour has brown color, slightly crunchytexture, slightly sweet taste and dominant of tempeh aroma. The elected cookies product in100 grams contains 506,8 kcal of energy, 37,2 grams of carbohydrtares, 23,35 grams of protein,29,4 grams of fat and 9,98 grams of dietary fber.